Reasons For Justifying Media Crime - السراج عبود; المحمود علي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The crime may be committed and be completed for all its elements, however, the criminal responsibility of the perpetrator is not due to the existence of a reason for the absence of responsibility. Media crime, like any other crime, may be accompanied by a reason that raises the status of crime or prevents the criminal responsibility of the offender from occurring. The reasons for the absence of this responsibility in the media crime are of two types: The first type may relate to the victim in the case of consent issued before or during the commission of the act, or related to the offender, as in the case of force majeure and a state of necessity. The second type relates to media activity, which is the exercise of the right to publish news and permissible criticism. In our research, our study will be limited to the second type, which is one of the reasons for justification for media crime.